Machines & mechanisms applied kinematic analysis - Myszka, David H. (Merrill Prentice Hall, 2005)
Provides the techniques necessary to study the motion of machines, and emphasizes the application of kinematic theories to real-world machines consistent with the philosophy of engineering and technology programs. This book intents to bridge the gap between a theoretical study of kinematics and the application to practical mechanism.